Work requirements : race, disability, and the print culture of social welfare - Carmody, Todd, 1979- (Duke University Press, 2022)
"Work Requirements reframes the history of work-based social welfare practice as a representational project tasked with shoring up the inherent meaningfulness of work, examining what Todd Carmody calls the "print culture of social welfare" to show how work became an indicator of social deservingness over the late nineteenth and early twentieth centuries. Prior to the emergence of the formal US welfare state, textual projects-from documentary photographs to insurance claims-contributed to the idea that individuals must be engaged in work to deserve social welfare. Progressive charity reformers and advocates of Black industrial education pushed for social welfare reforms to make people with disabilities, poor people, people of color, and incarcerated people into wage-earning citizens. Carmody shows how the bootstrap narrative, Taylorist studies of labor, and nineteenth-century ideas of race and disability fed into a specific ideology about labor-particularly, that someone's willingness to work could be scientifically measured and systematically evaluated-that continues to shape US welfare policy today."--